On the porous thermoelastic system with Coleman–Gurtin law. Issue 13 (2nd September 2022) - Santos, M. L.; Cordeiro, S. M. S.; Maciel, E. S.
ABSTRACT: In this paper, we investigate a porous thermoelastic system where the heat conduction is given by Coleman–Gurtin's law. We show that the system is exponentially or polynomially stable depending on a relationship between the coefficients of wave propagation speed.